The role of cluster centre principals in the Ohangwena education region in Namibia - Nghatanga, Ponny Haggai (Rhodes University, Faculty of Education, Department of Education, 2011)
The Namibian Ministry of Education introduced the School Clustering System (SCS) in 1996. The system entails the grouping of schools into clusters to facilitate the sharing of resources and expertise. One school in a group is selected to serve as the Cluster Centre and the principal of the centre is identified as the Cluster Centre Principal (CCP). This has created a new level of educational leadership which is still relatively under-researched and the primary purpose of this study is to investigate the perceptions of this new role since it is perceived to be pivotal to the effective functioning of the cluster. This study is an interpretive case study of Cluster Centres in the Komesho Circuit in the Ohangwena Educational Region. Three data collection instruments were used, namely document analysis, observation and interviews. The collected data provided insight into participants' views on the role of Cluster Centre Principals (CCPs), which shed light on the challenges faCing the roles of CCPs. The findings revealed that respondents welcomed the decentralisation of an education system that involves cluster members and parents in decision making. Furthermore, the perceived role of CCPs is perceived as delegation through participative leadership and management approaches. This involves groups in teamwork to enhance the quality of teaching and learning. The study has, however, also exposed tensions surrounding the role and function of CCPs. This is partly because the role has not been formalised and is perceived as existing in a legal vacuum. This study will benefit the Cluster Centre Principals, Inspectors of Education, Advisory Teachers, non-governmental Organisations, the community and the Ministry of Education by placing the role of Cluster Centre Principals in perspective.
Keywords: School management and organization -- Namibia -- Ohangwena; School principals -- Namibia -- Ohangwena; Educational leadership -- Namibia -- Ohangwena; Educational change -- Namibia -- Ohangwena